Análise comparativa entre respostas de torre de transmissão sujeita a carregamentos obtidos através do método do vento sintético e da norma NBR 6123/88 - Leite, Emerson Batista (2015)
There are several procedures to determine the wind loadings. The Brazilian code NBR 6123/88 can be used to determine these loadings and the internal forces for structural design. However, there are non-normative procedures that may contribute to determining those same loads. One of them, which is used in this work, is the method of synthetic wind. The aim of this study is to make a comparative analysis of the responses obtained for the structure when subjected to dynamic loads, obtained through the synthetic wind method, and the responses obtained with static loads generated from considerations of NBR 6123/88 - Forces due to the wind on buildings. The structure under study is a power transmission tower, which is modeled in the software program RSTAB, developed by Dlubal, to determine its dynamic characteristics. Using the software Mathcad Prime 3.0 the dynamic wind loads are generated by an algorithm for the wind synthetic method. Static and dynamic loads are applied to in the structure to determine displacements, axial internal forces and support reactions. The compared results show that the approach that considers loadings generated from the NBR 6123/88 is the most conservative, with magnitude values that exceed up to 132% values obtained from the synthetic wind method.